Effect of Sewage Sludge Amendment on Heavy Metal Uptake and Yield of Ryegrass Seedling in a Mudflat Soil. Issue 2 (1st March 2013) - Gu, Chuanhui; Bai, Yanchao; Tao, Tianyun; Chen, Guohua; Shan, Yuhua
Abstract : Mudflat soil amendment by sewage sludge is a potential way to dispose of solid wastes and increase fertility of mudflat soils for crop growth. The present study aimed to assess the impact of sewage sludge amendment (SSA) on heavy metal accumulation and growth of ryegrass ( Lolium perenne L.) in a seedling stage. We investigated the metal availability, plant uptake, and plant yield in response to SSA at rates of 0, 30, 75, 150, and 300 t ha −1 . The SSA increased the metal availability in a mudflat soil and subsequently metal accumulation in ryegrass. The SSA increased the bioavailable fraction of the metals by 4550, 58.8, 898, 189, 35.8, and 84.8% for Zn, Mn, Cu, Ni, Cr, and Cd, respectively, at an SSA rate of 300 t ha −1 as compared to unamended soil. Consequently, the metal concentrations in ryegrass increased by 1130, 12.9, 355, 108, 2230, and 497% in roots and by 431, −4.3, 92.6, 58.3, 890, and 211% in aboveground parts, for Zn, Mn, Cu, Ni, Cr, and Cd, respectively, at the 300 t ha −1 rate as compared to unamended soil. The enhanced metal accumulation, however, did not induce growth inhibition of ryegrass. Fresh weight of aboveground parts and roots of ryegrass at 300 t ha −1 SSA rate increased by 555 and 128%, respectively, as compared to those grown in unamended soil. The study suggests that SSA can promote yield of ryegrass seedlings grown in mudflat soils. None of metal concentrations at all SSA rates was above the Chinese permissible limits. Despite the data at only the seedling stage, our results indicate that SSA in mudflat soils might be a potential way for mudflat soil fertility improvement and sewage sludge disposal. Further study at plants' maturity stage is warranted to fully assess the suitability of sewage sludge amendment on mudflat soils.